The Source of Iron‐Oxide Pigments Used in Pecos River Style Rock Paints. (16th January 2013) - Bu, K.; Cizdziel, J. V.; Russ, J.
<x xml:space="preserve">Abstract</x> The likely sources of iron‐oxide pigments used in prehistoric rock paintings in the Lower Pecos Archaeological Region were identified on the basis of chemical fingerprinting using LA–ICP–MS. The chemical signatures of 13 red rock paint samples collected from two south‐west Texas sites were compared with three potential source materials (ochre, siltstone and rhyolite), and two pigment cakes (crayons) that were excavated near the sampling sites. The significant chemical similarities between the paint and siltstones suggest that siltstone was used as the source of the colour. The overlapping chemical signatures for one of the pigment cakes and siltstone further suggests that some of the prehistoric people inhabiting the area 3000–4000 years ago had acquired the skills to extract iron oxide from siltstone and process it into paint pigments.